MILITARY LAW ENFORCEMENT STRATEGY OF SOLDIERS IN ORDER TO SUPPORTTHE MAIN TASKS OF THE INDONESIAN ARMY (CASE STUDY AT DENPOM I/6 BATAM): Strategi Penegakan Hukum Militer Prajurit Dalam Rangka Mendukung Tugas Pokok TNI Angkatan Darat(Studi Kasus di Denpom I/6 Batam) - Atep Priatna; Mhd. Halkis; Hipdizah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Military law enforcement is a fundamental element in maintaining the discipline and integrity of Indonesian Army (TNI AD) soldiers. This study aims to analyze military law enforcement strategies at Denpom I/6 Batam to support the primary tasks of TNI AD, particularly in addressing challenges such as high rates of desertion, drug abuse, and misuse of authority. Using a descriptive qualitative method, the study identifies various internal and external factors influencing the effectiveness of law enforcement. The findings reveal that key challenges include limited resources, suboptimal supervision, and the impact of interactions with civilian communities. To address these challenges, the study formulates strategies based on the use of information technology, specialized military law training, and cross-agency collaboration. The implementation of these strategies not only improves soldier discipline but also strengthens public trust in the TNI AD institution. The study recommends enhancing personnel capacity, modernizing support facilities, and establishing cross-sectoral collaboration mechanisms to achieve more adaptive and responsive military law enforcement